An elusive vinyl radical isolated as an appended unit in a five-coordinate Co(iii)–bis(iminobenzosemiquinone) complex formed via ligand-centered C–S bond cleavage. Issue 70 (21st July 2016) - Sarkar, Prasenjit; Tiwari, Archana; Sarmah, Amrit; Bhandary, Subhrajyoti; Roy, Ram Kinkar; Mukherjee, Chandan
Abstract : An unprecedented stable vinyl radical-containing Co(iii )–bis(iminobenzosemiquinone) complex formed by ligand-centered C–S bond breaking. Abstract : Redox-active ligand H4 Pra edt(AP/AP) experienced C–S bond cleavage during complexation reaction with Co(OAc)2 ·2H2 O in the presence of Et3 N in CH3 OH in air. Thus, formed complex1 was composed of two iminobenzosemiquinone radicals in its coordination sphere and an unprecedented stable tethered-vinyl radical. The complex has been characterized by mass, X-ray single crystal, X-band EPR, variable-temperature magnetic moment measurements and DFT based computational study.